Macroeconomic factors and the perception of criminal justice in society: the role of shadow economies1 - CESNIENE, ILONA; DOBRYNINAS, ALEKSANDRAS; GIEDRAITIS, VINCENTAS (Kriminologijos studijos, 2014)
The purpose of the present research was to investigate the relationship between economic factors and public attitudes toward contraband as well as emotional responses to the criminal justice system. Our analysis is based on a macro-economic analysis based on world-systems theory’s upswings and downswings in economic growth (and subsequent unemployment and inflation). Additionally, interview data provide an individual explanation about perceptions of criminal justice in society. We argue that perceptions of criminal justice are based on the general economic conditions of society. In an economic downswing, individuals may be forced to take more risks in order to prosper or survive and that may be seen as ‘allowed’ and ‘normal’ behaviour under those conditions. As such, perceptions of criminal justice (and what is crime) may be viewed with greater tolerance. Our interview results suggest that the black market is a form of proxy indicator for perceptions of criminal justice in society. Interview results show a much greater tolerance of contraband during times of economic hardship. Men, the poor, and those less satisfied with their lives were found to be more likely to buy contraband.Key Words: criminal justice, public attitude, emotional response, contraband.